Critical Care in the Military Health System: A Survey-Based Summary of Critical Care Services. Issue 11 (29th March 2018) - Nam, Jason J; Colombo, Christopher J; Mount, Cristin A; Mann-Salinas, Elizabeth A; Bacomo, Ferdinand; Bostick, Adam W; Davis, Konrad; Aden, James K; Chung, Kevin K; McCarthy, Mary S; Pamplin, Jeremy C
Abstract: Introduction: Critical care is an important component of in-patient and combat casualty care, and it is a major contributor to U.S. healthcare costs. Regular exposure to critically ill and injured patients may directly contribute to wartime skills retention for military caregivers. Data describing critical care services in the Military Health System (MHS), however, is lacking. This study was undertaken to describe MHS critical care services, their resource utilization, and differences in care practices amongst military treatment facilities (MTFs). Materials and Methods: Twenty-six MTFs representing 38 adult critical care services or intensive care units (ICUs) were surveyed. The survey collected information about organizational structure, resourcing, and unit characteristics at the time of a concurrent 24-h point-prevalence survey designed to describe patient characteristics and staffing in these facilities. The survey was anonymous and protected health information was not collected. We analyzed the data according to high capacity centers (HCCs) (≥200 beds) and low capacity centers (LCCs) (<200 beds). Differences between HCCs and LCCs were compared using Fisher's exact test. Results: Seventeen MTFs (7 HCCs and 10 LCCs), representing 27 ICUs, responded to the survey. This was a 65% response rate for MTFs and a 71% response rate for services/ICUs. HCCs reported more closed vs. open ICUs; more dedicated critical care services (i.e., medical and surgical ICUs vs. mixed ICUs); fewer respiratory therapists available, but more with certification; more total nursing staff and more critical care certified nurses; the use of subjectively more effective protocols (10.5 vs. 6.7 protocols/unit or service); higher utilization of an ICU daily rounds checklist (65% vs. 0%); and less consistency of clinician type participation during multidisciplinary rounds. ICU leadership structure was similar among the institutions. The majority of respondents were unable to provide summary APACHE II scores, but HCCs were more likely to submit this information than LCCs. Most centers perform multidisciplinary rounds daily, but they are more likely to be run by a physician credentialed in critical care at HCCs (85% vs. 59%, p < 0.05). 67% of respondents reported mortality rates <5%. The two services that reported mortality rates greater than 10% were both LCCs. Conclusion: This is the first comprehensive report about MHS critical care services. Despite notable variability in data reporting, an important finding itself, this study highlights notable differences in organizational structure and resourcing between HCCs and LCCs within the MHS. The clinical implication of these differences (i.e., impact on patient outcomes) of these differences require further study. Better understanding of MHS critical care services may improve enterprise decision-making about these services which could ultimately improve care of combat casualties.